Clinical-epidemiological profile of hospitalized children and adolescents by head trauma - João Ananias Machado Filho; Anamaria Cavalcante e Silva; Márcia Maria Tavares Machado; Rodrigo Araújo Madureira; Francisco Heron Alves de Carvalho; Lara Ribeiro Santiago; Luciano Lima Correia (Universidade de Fortaleza, 2010)
with Traumatic brain injury (TBI) and to analyze the severity of head trauma. Methods: A retrospective study evaluating 333 medical records of children and adolescents (0-19 years), admitted between June/2002 to July/2004 at a referral hospital for neurosurgery, in Cariri-CE, Brazil. Results: Most patients were male (70.3%), predominantly between 15-19 years. Mild trauma occurred in 73.3% (p = 0.294) of males, aged 5 years (88.9%, p = 0.048). Moderate to severe trauma occurred between 15-19 years (35.3%). As the main causal factors were identified falls from height (48.1%) and motorcycle (47.1%). Conclusion: The cases of TBI indicate high prevalence of severe cases, with the prevalence of falls and motorcycle accidents. The admissions in the neurosurgery service point to a public health problem of violence by the factors involved, especially the traffic, being necessary preventive and control measures, as from enforcement of traffic laws.